Tatbīq Ṭarīqat "Ḥalaqat Al-Musyāwarah" Li-Kitāb At-Turāṯ Li-Tarqiyati Mahārat Al-Qirā’ah Ladā Aṭ-Ṭullāb - Muhammad Arazi; Abdul Qodir (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study was motivated by the limited maharah qira'ah (Arabic reading proficiency) of students in reading and comprehending kitab turats (classical Islamic texts), resulting from the complexity of classical Arabic and the predominance of teacher-centered instructional approaches. Accordingly, this study aims to analyze the implementation of the Halaqah Musyawarah method in the learning of kitab turats and examine its contribution to improving students' maharah qira'ah at Madrasah Muallimin Hasyim Asy'ari Tebuireng Jombang. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. The participants included the head of the Islamic boarding school, musyrif (learning supervisors), and students participating in the Halaqah Musyawarah program. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the Halaqah Musyawarah method is systematically implemented through reading kitab turats, collaborative discussions, textual interpretation, grammatical analysis (nahwu and sharaf), scholarly deliberation, and continuous guidance from the musyrif. This student-centered and collaborative learning model significantly improves students' ability to read unvowelled Arabic texts fluently, comprehend classical Islamic texts accurately, analyze linguistic structures, and present academic arguments based on kitab turats. Its successful implementation is supported by competent musyrif, strong student motivation, a conducive Islamic boarding school environment, and the availability of classical Islamic texts as learning resources, although challenges remain in the varying levels of students' mastery of Arabic grammar, limited instructional time, and low self-confidence among some learners. This study contributes by proposing Halaqah Musyawarah as an effective collaborative learning model for enhancing maharah qira'ah while simultaneously strengthening critical thinking, linguistic analytical skills, and academic communication, thereby offering an alternative competency-oriented approach to the teaching of kitab turats and Arabic language education in Islamic boarding schools.